Constructing Authentic Identities in Recovery: Write of Passage. Issue 4 (2nd October 2017) - Howell, Charles; Fall, Kevin A.
ABSTRACT: The concept of identity is one aspect that can be explored to deepen a wide range of treatment approaches. This article seeks to outline a group approach based on narrative theory, which addresses identity issues in an innovative way to positively affect the creation of a more positive identity and positively impact long term recovery.